Efek anthiperkolesterol snack bars beras ketan hitam (Oryza sativa var. glutinosa) labu kuning (Cucurbita moschata) pada tikus Sprague dawley - Mustofa, Akhmad; Nugraheni, Ratna Dewi; Suhartatik, Nanik (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
Snack bars from black glutinous rice and yellow pumpkin powder has been developed. The aim of the research was to evaluate the effect of the snack bars to the lipid profile of white male rats Sprague dawley. The experimental design of the research was Pre-Post Test Randomized Control Group Design using 25 male white rats. The rats were divided randomly into 5 groups, which was Group 1 as negative control (standard feed), Group 2 as positive control (feed with lard for hyper cholesterolemia condition, Group 3 was treated with simvastatin (0.18 mg / 200gBB), Group 4 treated with snack bars A (450mg / kgBB) and Group 5 was treated with snack bars B (450mg / kg BB). The differences between snack bar A and B were the proportion of black glutinous rice and yellow pumpkin powder. The snack bar was given orally. Total cholesterol, HDL, LDL, and triglycerides after 14 days of the treatment. According to the statistical analysis (p<0.05), the results showed that group with simvastatin has no significant differences with group with snack bars A.Â  Group with simvastatin, snack bars A, and snack bars B significantly influence blood cholesterol levels, total cholesterol, triglyceride levels, and LDL levels.Â  Mainly, snack bars A could decline blood cholesterol as good as simvastatin. Snack bars A have a higher portion of black glutinous rice than snack bars B.